Digital Labour in the University: Understanding the Transformations of Academic Work in the UK - Jamie Woodcock (tripleC: Communication, Capitalism & Critique)
Universities have been the site of a variety of shifts and transformations in the previous few decades. Both the composition of students and academics are changing (to a lesser or greater extent), along with the ways in which teaching and research is supported, conducted, and delivered. The effects of neoliberalism, privatisation, precarious employment, debt, and digitalisation have been highlighted as important factors in understanding these changes. However, the ways in which these tendencies are expressed in universities – both in specific and general ways – remain fragmented and under-analysed. In particular, the role of academic labour processes, increasingly mediated through digital technology, remains in the background. There is a risk of viewing these transformations as abstracted, far removed from the day-to-day activities of academic labour on which universities rely. This article will therefore focus on connecting the broader changes in funding, organisation, and digital technology to the labour processes of academics. Rather than seeking a return to a romanticised pre-neoliberal university, this article explores the possibilities of resistance and alternatives to the university as it is now.